Serum oxytocin levels are elevated in body dysmorphic disorder and related to severity of psychopathology. (March 2020) - Fang, Angela; Jacoby, Ryan J.; Beatty, Clare; Germine, Laura; Plessow, Franziska; Wilhelm, Sabine; Lawson, Elizabeth A.
Highlights: We examined endogenous serum oxytocin levels in body dysmorphic disorder. People with BDD displayed higher oxytocin levels. Higher oxytocin levels significantly correlated with BDD symptom severity. Abstract: The neurobiological mechanisms underlying the pathophysiology of body dysmorphic disorder (BDD) are not well-understood. Oxytocin is a central nervous system peptide which regulates socioemotional functioning and may mediate physiologic processes in a range of psychiatric disorders, particularly those characterized by interpersonal dysfunction. Examining the role of oxytocin in the development and maintenance of BDD may elucidate new targets for intervention. The present study examined endogenous serum oxytocin levels in BDD. Given the prominent deficits in social functioning in BDD, we expected that BDD would be characterized by low basal serum oxytocin concentrations, relative to healthy controls, and that low oxytocin levels would be associated with BDD symptom severity as well as poor performance on measures of social cognition. Twenty individuals with BDD and 28 healthy controls completed a fasting blood draw consisting of frequent sampling every five minutes for one hour to measure pooled levels of oxytocin. Contrary to our hypotheses, people with BDD displayed higher concentrations of oxytocin, compared to their healthy control counterparts, and their oxytocin levels were positively correlated with BDD symptom severity. There were no associations between oxytocin levels and measures of social cognition. These findings suggest increased production of endogenous oxytocin in BDD. Prospective research is needed to determine whether this contributes to or is a consequence of BDD symptomatology.